Chapter Round Table comment: From «useful knowledge» to a «culture of growth» - Denzel, Markus A. (Datini Studies in Economic History, 2023)
we can state that economically useful knowledge could induce innovations which further deepened and widened this economically useful knowledge; and this cycle was at least one of the decisive factors of raising profitability and, as a final con-sequence, of economic growth becoming obvious in the industrial evolutions in different European and later also non-European countries. To say it more clearly: Innovations did influence economic growth. Cultural and institutional processes, which generated knowledge and human capital, could influence the development of labour productivity. Knowledge did contribute to reduce risks in pre-industrial societies through information, communication, and resilience